Two Authors and Their Two Books Writ Twice: James Tunstead Burtchaell and Rosemary Haughton, Twenty-Five and Thirty Years on - McDonough, William (Horizons, 2000)
James Tunstead Burtchaell had been teaching Rosemary Haughton's 1967 book The Transformation of Man for a number of years when he published Philemon's Problem in 1973. Now, with both authors having reworked their books in the last two years, we are given an opportunity to compare and contrast the development of Burtchaell's and Haughton's thinking on how grace transforms human beings. The present essay sees an intellectual convergence between Haughton and Burtchaell; it sees much to be grateful for in both books by both authors; and it claims that Haughton's new book has developed her thinking on grace's communal character further than Burtchaell's new book has developed his thinking on the same topic.